Corporate Social Responsibility Disclosure and Financial Performance of Banks in Indonesia - Nurdin, Maryam (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study examines the effect of Corporate Social Responsibility (CSR) on financial performance and stock returns in banking companies listed on the Indonesia Stock Exchange for 2020-2022. This research uses a quantitative approach with secondary data as the primary source. The research sample was selected using the purposive sampling method, resulting in 47 issuers as research objects. The data analysis technique used Statistical Product and Service Solution (SPSS) software, which allows in-depth analysis of the relationship between CSR variables and financial performance and stock returns. The results showed that CSR disclosure positively and significantly influences financial performance, as measured by Return on Equity (ROE). In addition, CSR also indicates a positive and significant influence on stock returns. These findings suggest that CSR disclosure is a corporate social responsibility and an effective business strategy to create added value. With higher CSR disclosure, companies can increase investor confidence, attract market interest, and strengthen their reputation, ultimately impacting growing profits and stock market stability. This study implies that companies, particularly in the banking sector, must strengthen CSR disclosure as part of their business strategy. Transparent CSR disclosure not only improves the competitiveness of companies in the capital market but also supports long-term sustainability. The findings are also relevant for regulators to design policies encouraging accountability and transparency in CSR reports, creating a more stable and sustainable investment environment.